(untitled) (Modern education and development, 2025)
This article explores the importance of reading as a tool for understanding and analysing global problems such as climate change, poverty, inequality, and international conflict. It highlights how reading various sources develops critical thinking, empathy, and global awareness. The article also discusses the role of reading in education and how it prepares students to be informed global citizens.